Native Speaker Interaction with Young Learners in English Class - Hybrid Learning Models - Hariyanti Lestari; Didin Nuruddin Hidayat; Nida Husna; Alek Alek; Anita Anita (Loquen, 2022)
The purpose of this study is to examine a native speaker's interaction with young learners in an English class to determine (1) what types of sentences she used in instructing young learners and (2) what tenses she used in giving instruction and asking questions while teaching young learners in the classroom. The researcher used the qualitative descriptive technique in order to perform the investigation. The information was gathered via class observation, including recording three meetings' worth of teaching and learning activities. After that, the tape was transcribed to analyze the data. The participants were a native English speaker and young learners from grade two primary students. The study's results reveal that the native speaker used various phrase types in her instruction, including simple, compound, complex, and compound-complex sentences. However, the most type of sentence she used is a simple sentence followed by a compound-complex and complex sentence. A minor type of sentence she used is a compound sentence. She also used three distinct tenses during her teaching. They exist in the present, the past, and the future. The most type of tenses she used was present and future tense. She almost rarely used past tense.